Motion activity and physical fitness of students in comprehensive schools of Karaganda city. (Journal of Educational Sciences, 2016)
The article deals with the issues of motion activity (MA) of comprehensive school students in vocational and technical educational establishments. There are the quantitative and qualitative indicators of daily motion activity: locomotion number, motional component, energy expenditure. The article also presents the quantitative and qualitative indicators of physical fitness: speed, speed-and-power performance, power and coordination abilities, flexibility and endurance of adolescents studying in comprehensive schools of Karaganda city. The analysis of students’ absolute measures of physical fitness indicators was carried out. Students who are not involved in doing any sports have low indicators of daily motion activity which do not meet health and hygienic standards. 40-60% of adolescents suffer from hypokinesia and perform low physical fitness indicators which do not correspond to the middle level of their development whereas the indicators of those students who go in for sports meet the hygienic standards. The author is giving practical recommendations.
Keywords: daily motion activity; locomotion; motional component; energy expenditure; physical fitness indicants